PENULISAN KALIMAT EFEKTIF SOAL CERITA DALAM BIDANG STUDI MATEMATIKA SEKOLAH MENENGAH PERTAMA DAN ATAS - Iib Marzuqi (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2016)
One of the problems faced by students in understanding about the story so often make mistakes, misinterpretation of the language, the students' mistakes in turning about the story (applied) mathematics in the form of everyday language. Of these problems, this research aimed (1) to describe the use of a wide variety of language diction about the story in the field of Mathematics from secondary school and (2) to describe the effective use of a wide variety of language sentences about the story in the field of study Mathematics. This study used a qualitative approach that is descriptive. From the research result, the use of diction lack of proper consists of four things, namely: (1) using less careful in the choice of concept or meaning of the word, (2) usingless careful in the choice of the form of words, (3) usingless accurate in the choice of language diversity, and (4) using less careful in the choice of function words, and phrases that are less effective include five things, namely: (1) using a sentence that is less possess integrity, (2) using a sentence that is less economical or less saving, (3) using the phrase is ambiguous, (4) using a sentence that is less aligned, and (5) using the phrase is less logical.